Experiences Using a Multidisciplinary Model for Treating Injection Drug Use Associated Infections: A Qualitative Study - Nolan, Nathanial S.; Gleason, Emily; Marks, Laura R.; Habrock-Bach, Tracey; Liang, Stephen Y.; Durkin, Michael J. (Frontiers in Psychiatry, 2022)
Background: Over the past two decades, the United States has experienced a dramatic increase in the rate of injection drug use, injection associated infections, and overdose mortality. A hospital-based program for treating opioid use disorder in people who inject drugs presenting with invasive infections was initiated at an academic tertiary care center in 2020. The goal of this team was to improve care outcomes, enhance patient experiences, and facilitate transition from the hospital to longer term addiction care. The purpose of this study was to interview two cohorts of patients, those admitted before vs. after initiation of this program, to understand the program’s impact on care from the patient’s perspective and explore ways in which the program could be improved. Methods: Thirty patients admitted to the hospital with infectious complications of injection drug use were interviewed using a semi-structured format. Interviews were transcribed and coded. Emergent themes were reported. Limited descriptive statistics were reported based on chart review. Results: Thirty interviews were completed; 16 participants were part of the program (admitted after program implementation) while 14 were not participants (admitted prior to implementation). Common themes associated with hospitalization included inadequate pain control, access to medications for opioid use disorder (MOUD), loss of freedom, stigma from healthcare personnel, and benefits of having an interprofessional team. Participants in the program were more likely to report adequate pain control and access to MOUDs and many cited benefits from receiving care from an interprofessional team. Conclusions: Patients with opioid use disorder admitted with injection related infections reported improved experiences when receiving care from an interprofessional team focused on their addiction. However, perceived stigma from healthcare personnel and loss of freedom related to hospitalization were continued barriers to care before and after implementation of this program.